Pengaruh Brand Image, Lifestyle Dan Promosi Terhadap Keputusan Pembelian Sepatu Ventela (Studi Kasus Pada Konsumen Toko Gorilla Market Bululawang) - Agung Prayitno; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine and analyze the influence of brand image, lifestyle, and promotion variables on the purchasing decision of Ventela shoes at the Gorilla Market Bululawang Store simultaneously or partially. The population in this study were all consumers of  Toko Gorilla Market Bululawang. Samples were taken using the formula from Maholtra's theory, in order to obtain 100 respondents who met the requirements as a sample. The type of data used is primary data. Data collection was carried out by distributing questionnaires to respondents. The technique used to analyze multiple linear regression. The results of this study indicate that (1) There is a simultaneous influence between Brand Image, Lifestyle and Promotion variables on Ventela Shoe Purchase Decisions at Gorilla Market Bululawang Stores consumers (2) Brand Image variables have an effect on Purchasing Decisions in consumers of Gorilla Market Bululawang Stores (3) Lifestyle variables have an effect on Purchasing Decisions in consumers of Gorilla Market Bululawang Stores and (4) Promotion variables have an effect on Purchasing Decisions in consumers of Gorilla Market Bululawang Stores. Keyword : Brand Image, Lifestyle, Promotion, Purchasing Decisions